Piece wapiennicze z południowo-zachodniej strefy osadnictwa kultury wielbarskiej w fazie lubowidzkiej na tle porównawczym – przegląd źródeł - Michałowski, Andrzej; Teska, Milena (Folia Praehistorica Posnaniensia, 2015)
This article is intended to complement the present state of knowledge on the lime production conducted in the area covered by the settlement of the Wielbark culture in the earlier stage of its development. The article includes a review of available evidence of such a production, reflected within a settlement by the presence of a lime kilns. The article focuses mainly on the presence of such features in the south-western area occupied by the Wielbark communities.